FeCl3-silica: A green approach for the synthesis of nitriles from oximes. Issue 8 (17th April 2016) - Ghosh, Pranab; Pariyar, Gyan Chandra; Saha, Bittu; Subba, Raju
ABSTRACT: A green and suitable protocol for the conversion of aldoximes into nitriles is described. The transformation is carried out under solvent-free conditions using FeCl3 -silica medium. The protocol offers a green, single-step facile procedure with the use of less toxic metal salt to isolate nitriles in good to excellent yields. GRAPHICAL ABSTRACT: